Channel coding optimisation for bandlimited DS-CDMA systems - Li, Kwet Pin Chi Van. (2008)
In this thesis, the trade-off between channel coding and PN-spreading is investigated in order to optimize the BER and user capacity performances of bandlimited DS-CDMA operating in practical fading channels.